Production and characterization of anti-dengue capsid antibodies suggesting the N terminus region covering the first 20 amino acids of dengue virus capsid protein is predominantly immunogenic in mice - Chunya Puttikhunt (2018)
We produced monoclonal and polyclonal antibodies to the capsid (C) protein of dengue serotype 2 virus (DV2 C). First, a maltose-binding protein fused to DV2 C protein (MBP-C) was overproduced in E. coli. The affinity-purified MBP-C protein was cleaved by factor Xa protease to obtain a recombinant DV2 C protein, which was then used for mouse immunizations. Two hybridoma cell lines producing anti-C Mabs as well as anti-C polyclonal antibody were successfully generated and characterized. Interestingly, all of the generated antibodies specifically recognized the first 20 amino acids of the DV2 C protein, as determined by peptide epitope mapping and via a recombinant DV2 C protein in which this region was deleted. The results suggested that this region is predominantly immunogenic in mice. © Springer-Verlag 2009.